RANCANGAN MANUFAKTUR SEAL UNTUK SPRAYBALL PROJECT PADA MESIN DYEING TEKSTIL - Frans Daniel Parmonangan Sinambela, (2023)
In the textile industry, in the dyeing process, the cleaning process is one of the processes used. The working principle of the cleaning process uses the principle of pressure water which can increase efficiency in the use of clean water used by 50% when compared to conventional cleaning processes. There are variables that affect the cleaning process, namely the use of seals aims to improve the cleaning process. From the results of a visual inspection, after the cleaning process ended, it was seen that there was a defect in the bottom seal of the sprayball tool after use. In this study the aim is to improve the quality of the seal so that no damage occurs from environmental factors when used and can last longer. From the research results obtained, it can be concluded that using the DFM method can improve seal quality and efficient production processes.